Experimental study of skull bones reconstruction with the use of autografts and hydroxyapatitical gel - Ismagilov, E. R.; Karas, A. F.; Karas, G. A. (Journal of Education, Health and Sport, 2018)
Introduction. To conduct reconstructive surgical interventions at pathological processes of skull base bone, defects of the temporal bone and dura mater, is especially complicated with the appearance of liquorrhea. This necessitates the improvement of operative technique and the use of new plastic materials. Objective: to study the features of meninges and skull bone defects plastic using autobone, fascia and HAP gel based on clinical observation, and macroscopic and microscopic experimental studies. Materials and methods: 36 mature nonlinear rats of both sexes up to 6 months old, weighing 190-250 g were divided into 2 groups. In the 1st (experimental) group there were 18 animals and autofragments of fascia and tibia with the addition of GAP gel were used for implantation; and in the 2nd group (comparison, n=18) the same plastic material without gel was used. The introduction of implant was carried out under general anesthesia in a standardized defect of skull frontal bones. The method of clinical observation, stereoscopic, common histological examination after staining with hematoxylin-eosin was applied. Results: The introduction of bone’s and fascia autografts into skull defect and dura mater provides the structural function of the damage tightly closing, preventing or stopping of liquorrhea, besides fascia contributes to vascularization of tissues in the healing zone. Additional administration of HAP ge, provides pronounced adhesion to bone tissue, gaps filling in the graft bed, creates a microenvironment for metabolism in the zone, shows a positive effect on osteogenesis, promotes calcification and bone reconstruction in the area of the defect. The results obtained also indicate the peculiarities of reparative processes in the bones of the skull, expressed in the dependence of bone repair and / or the development of fibrous tissue in the defect area and the density of adherence of the bone to the mother tissue, which is accompanied by improved bone restructuring under tight contact of the mother bone with the implanted material and the prevalence of fibrous tissue in case of their violation. This data confirm the effectiveness and promise HAPG use along with autofascia and autobone to close the defects of the meninges and skull bones and are important for improving reconstructive-restorative surgical interventions.